(Invited) Intrinsic Reliability Assessment of 650V Rated AlGaN/GaN Based Power Devices: An Industry Perspective. (4th May 2016) - Moens, Peter; Banerjee, Abhishek; Constant, Aurore; Coppens, Peter; Caesar, Markus; Li, Zilan; Vandeweghe, Steven; Declercq, Frederick; Padmanabhan, Balaji; Jeon, Woochul; Guo, Jia; Salih, Ali; et al.
Abstract : Although astounding performance is already proven by many research papers, the widespread adoption of GaN power devices in the market is still hampered by (1) yield and reproducibility ; (2) cost ; (3) reliability. All three factors are to be considered, but to convince customers to adopt GaN power devices, proven device and product reliability is a must. Cost is kept acceptably low by growing the GaN epi stack on 6 inch and 8inch Si substrates, and by processing the GaN power device technology in standard CMOS production lines. This paper will focus on the most important intrinsic reliability mechanisms for GaN power devices. It will cover gate dielectric reliability, Ohmic contact reliability, accelerated drain stress testing (high temperature reverse bias--HTRB) and high voltage device wear-out testing (high voltage off-state stress--HVOS). Acceleration models are discussed A measurement strategy to extract valuable information about the physical properties of the buffer layers (e.g. activation energies of the traps, conduction mechanisms, …) based on simple transmission line structures, is outlined.